Peningkatan Kedisiplinan pada Mata Pelajaran Matematika melalui Model Pembelajaran Kooperatif Jigsaw Siswa Kelas 3 Sekolah Dasar - Amalia, Renata Rizky; Utomo, Arief Cahyo (FONDATIA, 2024)
This classroom action research aims to determine the impact of implementing the jigsaw type cooperative learning model on improving students' disciplinary attitudes in mathematics subjects. This research was carried out in the 2023/2024 academic year. This research was carried out in 2 cycles in class III of SD N Trangsan 1, Sukoharjo, consisting of 12 girls and 6 boys. The data analysis technique was carried out using a quantitative descriptive approach through success indicators which were used to measure the achievement of a disciplined attitude in the learning process in mathematics lesson content. Based on the results of research on disciplinary attitudes in cycle I, it was found that the average research results reached 70% which was in the sufficient category. Then in cycle II it reached 83% which was categorized as good. So it can be concluded that the jigsaw type cooperative learning model has been proven to be effective in improving students' disciplinary attitudes in mathematics subjects. This learning model can be applied as a learning model that is used to help teachers improve students' social and intellectual attitudes, especially discipline in learning mathematics.